JURIDICAL ANALYSIS OF LEGAL CIRCUMVENTION PRACTICES IN LAND OWNERSHIP TRANSACTIONS BY FOREIGN CITIZENS THROUGH NOMINEE AGREEMENT MECHANISMS IN INDONESIA - Maniah; Erniyanti; Soerya Respationo; Tartib (RADJA PUBLIKA, 2025)
This study examines notarial practice challenges in archipelagic regions through a comprehensive case study of Batam City, Indonesia, which serves as a unique example of an archipelagic special economic zone with significant cross-border commercial activity. The research employed mixed-methods methodology including in-depth interviews with 15 practicing notaries, focus group discussions with diverse client groups, and quantitative analysis of 384 notarial transaction records spanning 2019-2024. The findings reveal four primary challenges systematically affecting service delivery: geographical constraints causing average service delays of 2.8 days for island-based clients versus 0.6 days for urban clients; regulatory complexity with 89% of notaries reporting uncertainty about applicable legal frameworks among 47 potentially relevant regulatory provisions; technological limitations where only 23% of offices provide basic digital tools despite 82% of clients expecting digital services; and access disparities with island-based clients comprising merely 18% of service users while representing 31% of registered businesses. Statistical analysis demonstrates significant economic implications, showing that each additional day of notarial processing time correlates with a 1.2% decrease in investment completion probability, while transportation costs add 15-20% to total service expenses for island clients, creating systematic inequalities in legal service access. Professional development deficiencies further compound these operational challenges, with 71% of notaries feeling inadequately prepared for the complex regulatory environment they encounter in special economic zone practice. The research recommends four critical interventions: regulatory harmonization through integrated frameworks clarifying relationships between national notarial law and special economic zone requirements; controlled technology adoption programs enabling secure remote notarization while maintaining legal authenticity; restructured professional development programs addressing specialized knowledge needs of archipelagic practice; and innovative service delivery solutions including mobile notarial services and satellite offices to improve geographical accessibility. These findings contribute significantly to understanding legal service delivery in geographically challenging contexts and provide evidence-based foundations for comprehensive policy reform that could transform Indonesia's archipelagic geography from a barrier into a competitive advantage through context-specific innovations in notarial practice..